Driving social change : how to solve the worlds toughest problems - Light, Paul Charles. (Wiley, 2011)
"Social Breakthrough, from Dr. Paul Light of New York University, illustrates how to create the social breakthroughs needed to solve urgent global threats such as poverty, disease, and hunger. The book then turns to three alternative but complimentary paths to social breakthrough, (1) social protecting, (2) social exploring, and (3) social advocacy, and provides a detailed map of the journey from initial commitment to a world of justice and opportunity. The book includes: An examination of the current condition of the social impact infrastructure. Strategies for how to remedy the steady weakening of our social-impact infrastructure. Tactics to build strong social organizations and networks. Dynamic methods to respond to constant economic and social change."--